2003
DOI: 10.3136/fstr.9.342
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Carbon Dioxide Decreases the Heat Tolerance of the Bacterial Spores

Abstract: Effect of high pressure carbon dioxide treatment (35˚C, 6.5 MPa) (HPCT) on the heat tolerance of bacterial spores was investigated. Spores of Bacillus coagulans and B. licheniformis were subjected to HPCT following heat treatment (80, 85 and 90˚C for 30 min) (HT). Spores of both types were sterilized completely in 30 min-90˚C HT after HPCT. These results indicated that HPCT greatly decreased the heat resistance of spores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Watanabe et al (2003) showed that carbonation at ambient temperature induces loss of heat resistance in B. coagulans and B. licheniformis spores. This carbonation-mediated loss of heat resistance was also observed in B. subtilis spores under heating.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al (2003) showed that carbonation at ambient temperature induces loss of heat resistance in B. coagulans and B. licheniformis spores. This carbonation-mediated loss of heat resistance was also observed in B. subtilis spores under heating.…”
Section: Discussionmentioning
confidence: 99%
“…subtilis spores It is thought that dormant spores are easily inactivated by several pasteurization methods after germination (Watanabe et al, 2003). Pressure-mediated inactivation of spores was achieved by first initiating germination and then inactivating the germinating spores via hydrostatic pressure treatment (Sale et al, 1970).…”
Section: Effect Of Ch In the Presence Of MC 10 On Germination Of Bmentioning
confidence: 99%
“…Therefore, carbonation can be applied to liquid food with neutral pH, and is likely to replace or partially substitute currently and widely applied thermal processes (Spilimbergo and Bertucco, 2003). Previous studies have shown that carbonation with mild heating (<10 MPa, 20 _ 40℃) effectively inactivates vegetative bacterial cells and fungal cells (Watanabe et al, 2003). However, spores of various Bacillus species are metabolically dormant and are thus highly resistant to environmental stress factors (Ghosh and Setlow, 2009) including carbonation (Watanabe et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The cell deaths of Listeria monocytogenes, Bacillus cereus and Staphylococcus aureus (from 7 to 9 log reduction) caused by high-pressure CO 2 were found by many studies (Wei et al, 1991;Lin et al, 1994;Ishikawa et al, 1997;Sirisee et al, 1998;Erkmen, 2000dErkmen, , 2001aSpilimbergo et al, 2002Spilimbergo et al, , 2003aSpilimbergo et al, , 2003bSpilimbergo et al, , 2003cSpilimbergo and Bertucco, 2003;Kim et al, 2008). Wei et al (1991) 1994 1996 1998 2000 1986 1988 1990 1992 2002 2004 2006 2008 sample at 6.18 MPa, 35°C in 120 min for a nearly 9-log reduction effect, while the study of Watanabe et al (2003), at the same level of pressure, temperature and same water sample, found that pressurized CO 2 could deactivate Bacillus licheniformis by 7 log in only 10 min. Kobayashi et al (2012aKobayashi et al ( , 2012b began to draw attention to the inactivation effect of pressurized CO 2 bubbles in water and liquid samples.…”
Section: Gram-positive Bacteria Inactivationmentioning
confidence: 92%